Development of new effective activated carbon supported alkaline adsorbent used for removal phenolic compounds - Humadi, Jasim; Nawaf, Amer T.; Khamees, Luay Ahmed; Abd-Alhussain, Yasser A.; Muhsin, Hussain F.; Ahmed, Mustafa A.; Ahmed, Marwan M. (Communications in Science and Technology, 2023)
Phenolic (phenol) compounds are the major contaminates in wastewater, which can have a considerable negative influence on the environment and health of human. Adsorption is an efficient process that is widely applied in order to eliminate phenol in wastewater. In recent, Adsorption process has acquired a lot of attentiveness owing to its relative moderate operating conditions. However, adsorption process needs considerable ameliorations in terms of adsorbent modification, process type, productivity, and conversion rate. This work studies the development of a fast and effective adsorption process in a fixed bed adsorption column (FBAC) in order to reach safe and continuous elimination of phenolic compounds. Several adsorption parameters (reaction temperature, adsorbent bed height, feed flow rate and kind of adsorbent) were studied to achieve the highest removal of phenolic compounds. The adsorption process was conducted in the presence of two type of adsorbents (activated carbon (AC), and KOH/AC), 73% and 94% of phenol elimination were attained, respectively, at 10 cm bed height, 1 ml/s feed flow rate, and 75 °C reaction temperature. The adsorbents activity was investigated after six consecutive adsorption cycles at the best process conditions, and the adsorbents show high stability in terms of phenolic compounds adsorption. After that, the spent adsorbents were regenerated by utilizing various solvents (methanol, ethanol and iso-octane), and the results show that iso- octane achieved highest regeneration efficiency. The adsorption process was implemented in the adsorption column that the performance is possibly to be adjusted at an industrial scale since it can be scaled up predictably.